Persepsi dan Preferensi Masyarakat terhadap Infrastruktur Hijau Kota Yogyakarta - Ririk Darti Pratiwi; Indung Sitti Fatimah; Aris Munandar (http://arl.faperta.ipb.ac.id/, 2019)
Green infrastructure has been indicated as promising measure for adaptation to climate change impact, especially in densely populated cities where green spaces in a big scale were rare. Yogyakarta City expected would be a good representative case study, due the urban density and limited green spaces. In order to gain a better understanding and awareness of climate change impact and green infrastructure benefit, it is important to find out how people think about issues related to it. Perceptual studies can generate more understanding of the research areas, and knowing the preferences for implementing green infrastructure can help urban planners identify more effective policy responses. The objective of this study is to analyze public perceptions and preferences on climate change and green infrastructure in Yogyakarta City. The study area located in Yogyakarta City is divided into three groups based on the difference proportion of surface temperature. Data collecting conducted by online questionnaires, and samples selection used accidental sampling method. Descriptive statistics used to analyze descriptive data, chi square and Kruskal-Wallis analysis were used to determine the differences between three study areas, then logistic regression method used to find out the influence of socio-demographic factors. The results showed that there were not many significant differences between the 3 groups of study areas on community perceptions and preferences, while socio-demographic factors such as age, occupation, and gender affect some results of community perceptions and preferences. This study explains how community’s awareness of climate change impacts and understanding of the benefits of green infrastructure and local preferences, so that the benefits of green infrastructure can be accepted by the community effectively.